Rapid detection of porcine and bovine gelatins in dental prophylaxis pastes using fourier transform infrared spectroscopy - Dewi Ardini, Yunita; Lestari, Widya; Tajudin, Noor Ashikin; Abdul Azis, Nur Fatin (2015)

(untitled)
Objectives: To rapidly detect the presence of porcine or bovine gelatins in dental prophylaxis pastes used in Malaysia by using Fourier Transform Infrared Spectroscopy (FTIR). Materials and methods: Four commonly used dental prophylaxis paste brands in Malaysia were collected and labelled A, B, C, and D. Pure porcine and bovine skin gelatins were used as controls. Gelatin extraction was carried out using acetone precipitation method. The extracts were then placed in the FTIR Perkin Elmer spectrometer for less than 5 minutes. All spectra were recorded within 4000 - 400 cm-I wavenumber with 4 cm-I resolution under 40 scans. The results were analysed by comparing the samples' spectra with the controls'. The data were subjected to discriminant analysis using The Spectrum ™ Software. Results: Sample A and porcine gelatin spectra had similar peak at 2163 cm-I while sample B showed similarity to bovine gelatin at the range of 4000 - 2000 cm-I. Detailed analysis of the spectrum patterns of sample C in the area between 1600-1400 cm-I and 3600-2800 cm-I indicated an appearance of similar peaks to porcine gelatin. On the other hand, the spectrum of sample D at the range of 1800-1200 ern -I was similar to that of bovine gelatin. Conclusion: Bovine and porcine gelatins in dental prophylaxis paste can be rapidly detected using FTIR. Keywords: porcine gelatin, bovine gelatin, FTIR.